The Effect of Different Concentrations Addition of Cooked Rice as Carbohydrates Sources and Brown Sugars to the Quality “Bekasam” made of Red Tilapia (Oreochromis niloticus) - Azizah Nuraini; Ratna Ibrahim; Laras Rianingsih (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2014)
Bekasam is a product of fermentation of fish with an additional source of carbohydrates that have a taste salty and sour is typical, generally use freshwater fish. Processing bekasam in Kalimantan some use additional sugar as a source of carbohydrates. Data about the quality of the source with the use of carbohydrate bekasam rice already published. However, it has not yet obtained the data quality carbohydrate sources that use bekasam rice added brown sugar. The study aims to determine the effect of the different concentration of rice carbohydrate source and the addition of brown sugar in processing Red Tilapia fish bekasam during 7 days fermentation at room temperature on product quality in terms of its chemical and hedonic. The addition of rice carbohydrates sources 40% (b b-1) in the manufacture of Red Tilapia fish bekasam lowers the pH of the product, the value of TVBN, but increase total lactic acid, total sugars and amino acids lysine products, either without the addition of brown sugar or brown sugar with the addition of 3%. The addition of brown sugar 3% (b b-1) causes the levels of total lactic acid, total sugars and amino acids lysine and hedonik higher values compared to the product without the addition of brown sugar on the addition of carbohydrate source rice 35% or 40%. There is the interaction between carbohydrate source concentration differences of treatment of rice and sugar concentration differences of treatment with respect to the value of pH, total lactic acid, and amino acids lysine. The product is the best bekasam bekasam made rice a carbohydrate source with the addition of 40% (b b-1) by the addition of brown sugar 3% (b/b) with characteristic values of pH 4.66, total value of 0.90% lactic acid, sugar value total 4.20%, TVBN value 37.51 mgN (100gr)-1, amino acids lysine 0.65% and the value of hedonik 3.01 (preferred panelist). Keywords : Red Tilapia Fish; Bekasam; Coocked Rice; Brown Sugar; Quality